2009
DOI: 10.1097/hjr.0b013e3283294b1d
|View full text |Cite
|
Sign up to set email alerts
|

EUROASPIRE III: a survey on the lifestyle, risk factors and use of cardioprotective drug therapies in coronary patients from 22 European countries

Abstract: The EUROASPIRE III survey shows that large proportions of coronary patients do not achieve the lifestyle, risk factor and therapeutic targets for cardiovascular disease prevention. Wide variations in risk factor prevalences and the use of cardioprotective drug therapies exist between countries. There is still considerable potential throughout Europe to raise standards of preventive care in order to reduce the risk of recurrent disease and death in patients with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
471
4
84

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 747 publications
(585 citation statements)
references
References 51 publications
26
471
4
84
Order By: Relevance
“…The proportion of antiplatelet drug users at 6 months found in the present study was similar to that found in the EuroAspire III survey in the Netherlands 6. However, the proportion of antiplatelet drug users at 1 year in the present study was higher than that found in the Netherlands Heart Foundation (NHF) study, which reported 58–65% antiplatelet drug use at 1 year after MI hospitalization 16.…”
Section: Discussionsupporting
confidence: 81%
“…The proportion of antiplatelet drug users at 6 months found in the present study was similar to that found in the EuroAspire III survey in the Netherlands 6. However, the proportion of antiplatelet drug users at 1 year in the present study was higher than that found in the Netherlands Heart Foundation (NHF) study, which reported 58–65% antiplatelet drug use at 1 year after MI hospitalization 16.…”
Section: Discussionsupporting
confidence: 81%
“…Uma diretriz pode requerer, em média, um período de cinco anos para ser amplamente divulgada e suas recomendações passarem a ser transpostas para a prática clínica segundo mostrou o European Action on Secondary and Primary Prevencion by Intervention to Reduce Events III (EUROASPIRE III) 21 . A primeira diretriz de Prevenção da Aterosclerose na Infância e Adolescência foi lançada em 2005 e está prestes a completar o seu período de divulgação, sem, no entanto, ser conhecida por muitos profissionais, pelo menos na cidade de São Paulo.…”
Section: Discussionunclassified
“…The input parameters for G*Power 3.1 were the desired statistical power (0.8), moderate anticipated effect size (0.15), and standard deviations of the predictor (L den : ≈ 5-10 dB; noise annoyance: 2.27 -1.43) and outcome variables (SBP: 20.4 mmHg; DBP: 12.3 mmHg). The latter were elicited from Dzhambov and Dimitrova 25 and Kotseva et al 26 . Overall, 217 patients were included: 111 from SGUH, 57 from KUH, and 49 from SKH (participation rates > 95%).…”
Section: Sample Sizementioning
confidence: 99%